The Impact of Financial Technology Innovation and Trust Perception on Financial Transaction Interest Through the Risk of Using LPD Mobile - Trisnadewi, Ni Kadek Ayu (International Journal of Social Science and Business, 2025)
The adoption of digital financial services in rural Village Credit Institutions (LPDs) remains hindered by limited understanding of how financial technology (Fintech) innovation and perceived trust influence customer interest, particularly when mediated by the perceived risk of using LPD Mobile services. This study examined the relationship between Fintech innovation, perceived trust, risk of use, and interest in financial transactions in the context of the LPD Desa Adat Les-Penuktukan. A quantitative approach was employed, with data collected from 100 respondents using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that Fintech innovation had a positive and significant effect on both risk of use and transaction interest. Perceived trust also positively and significantly influenced risk perception and transaction interest. Risk of use was found to have a positive and significant impact on transaction interest, and it significantly mediated the effects of both Fintech innovation and perceived trust on transaction interest. These findings suggest that while Fintech innovation and trust encourage digital transaction adoption, the perception of risk remains a critical factor that can enhance or diminish this relationship depending on how it is managed. The study concludes that successful digital adoption in rural LPDs requires balanced technological advancement, strong institutional trust, and proactive risk management to sustain customer interest and engagement.